THE CORRELATION BETWEEN SELF-ESTEEM AND SPEAKING PERFORMANCE IN INDONESIA - Mutia Satriani (TLEMC (Teaching and Learning English in Multicultural Contexts), 2019)
This study purposes to discover the level of student’s speaking performance and to investigate the correlation between self-esteem and speaking performance in EFL context. This research is conducted due to the fact that speaking becomes a problem for many EFL senior high school students, proved by their low English speaking performance. The data are collected from 102 students consisting 51 males and 51 females. A speaking test in the form of role play and a closed-ended questionnaire adapted from a well-known self-esteem scale, an adult version of Coopersmith Self-Esteem Inventory (CSEI), are given to the students. The score is processed in SPSS Statistics 17.0 to determine the correlation between the two variables. The research findings show that the students’ English speaking performance stands on medium level and  there is a highly significant positive correlation between self-esteem and speaking performance in EFL context with the correlation coefficient obtained 0.731. It is suggested that students have to try to believe that they are competent and worthy so that they are not reluctant to speak in English language. Besides, school managements and teachers should also design school activities which can stimulate students’ self-esteem.